Double-transmitting and Sextuple-receiving Borehole Transient Electromagnetic Method and Experimental Study - Wang, Bo; Liu, Shengdong; Li, Shining; Zhou, Fubao (Earth Sciences Research Journal, 2017)
With the continuous improvement of precision requirements for borehole geophysical exploration, the application of transient electromagnetic method (from now on referred to as TEM) in a borehole has become a hot spot. The conventional borehole TEM can only determine the longitudinal depth of the geological anomaly, the radial azimuth and depth cannot be resolved. A double-transmitting and sextuple-receiving borehole TEM is proposed, through which the radial anomaly is excited by the electromagnetic field generated by the double-emitting loops, and the azimuth and depth of the anomaly will be identified by the difference characteristics of the six receiving loops signals. In this paper, the response equations of the transmitting-receiving mode of double-transmitting and sextuple-receiving borehole TEM are deduced, and the response characteristics of the induction segment and the attenuation segment of the receiving loops are obtained based on the response equations under ramp function turn-off condition, providing the basis for theoretical analysis. Due to the negative value of the double-transmitting and sextuple-receiving transient electromagnetic response signals, a negative transformation algorithm under the double logarithmic coordinate system is proposed to provide the essential method for the analysis of two kinds of physical simulation experimental data of the radial azimuth and radial depth detection of the anomaly. The results show that the double-transmitting and sextuple-receiving borehole TEM has decent resolution ability in detecting the radial azimuth of the anomaly, and the effective resolution is 30°. The geometric difference among induced voltages of different measuring points can be used to evaluate the radial depth of the anomaly qualitatively. It is expected that the double-transmitting and sextuple-receiving borehole TEM can provide technical guidance for little borehole geophysical exploration in the fields of oil, natural gas, coal and basic engineering construction.